Beginning GraphQL (Packt Publishing, 2018)
"This fast-paced course is specially designed for learning all aspects of GraphQL. You will start by understanding basic features of this language. You will learn how to integrate GraphQL with server-side applications, and how to implement the querying of data in real time. You will also discover ways to connect GraphQL with server-side applications using the Apollo client. By the end of the course, you will be able to successfully create fast client-server REST-like applications."--Resource description page